(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2023)
This research paper is devoted to one of the subsections of the science of hygiene – nutrition hygiene. Moreover, proper nutrition and some serious consequences of improper nutrition are also in the center of discussion of this scientific article. This scientific work was written to study and analyze: the impact of food products on human health and development; prevention of negative consequences that may occur as a result of body saturation; increasing the benefit of consumed food; studying the characteristics of a person’s diet based on his sex, age and constitutional characteristics.